Implantable Cardioverter-Defibrillators in Trials of Drug Therapy for Heart Failure - Gama, Francisco (2020)
BACKGROUND Medical therapy for heart failure with reduced ejection fraction evolved since trials validated the use of implantable cardioverter-defibrillators (ICDs). We sought to evaluate the performance of ICDs in reducing mortality in the era of modern medical therapy by means of a systematic review and meta-analysis of contemporary randomized clinical trials of drug therapy for heart failure with reduced ejection fraction. METHODS AND RESULTS We systematically identified randomized clinical trials that evaluated drug therapy in patients with heart failure with reduced ejection fraction that reported mortality. Studies that enrolled <1000 patients, patients with left ventricular ejection fraction >40%, or patients in the acute phase of heart failure and study treatment with devices were excluded. We identified 8 randomized clinical trials, including 31 701 patients of whom 3631 (11.5%) had an ICD. ICDs were associated with a lower risk of all-cause mortality (relative risk [RR], 0.85; 95% CI, 0.78-0.94) and sudden cardiac death (RR, 0.49; 95% CI, 0.40-0.61). Results were consistent among studies published before and after 2010. In meta-regression analysis, the proportion of nonischemic etiology did not affect the associated benefit of ICD. CONCLUSIONS In our meta-analysis of contemporary randomized trials of drug therapy for heart failure with reduced ejection fraction, the rate of ICD use was low and associated with a decreased risk in both all-cause mortality and sudden cardiac death. This benefit was still present in trials with new medical therapy.